The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1007/s11099-015-0162-x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of vermicompost fertilizer on photosynthetic characteristics of chickpea (Cicer arietinum L.) under drought stress

Abstract: Water availability is an important factor for plant growth in arid environments. In recent decades, vermicompost (VC) fertilizer has been used in agriculture as a safe and effective fertilizer with high water-holding capacity. The aim of the present study was to characterize effects of VC fertilizer on photosynthetic activity of chickpea (Cicer arietinum L. cv. karaj) under drought conditions at three growth stages. Tests were done at five volumetric ratios of vermicompost to soil: 0:100, 10:90, 20:80, and 30:… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

6
67
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 88 publications
(73 citation statements)
references
References 27 publications
6
67
0
Order By: Relevance
“…Sadeghi-Shoae et al [2014] reported that methanol foliar application increased total dry matter (TDM), root yield (RY), sugar yield (SY) and white yield sugar. In addition, methanol application had alleviating impacts on chickpea exposed to drought stress conditions [Hossinzadeh et al 2012]. Bagheri et al [2014] reported that spraying with 20% (v/v) methanol in lavender greatly increased leaf area, leaf fresh and dry mass.…”
Section: Introductionmentioning
confidence: 99%
“…Sadeghi-Shoae et al [2014] reported that methanol foliar application increased total dry matter (TDM), root yield (RY), sugar yield (SY) and white yield sugar. In addition, methanol application had alleviating impacts on chickpea exposed to drought stress conditions [Hossinzadeh et al 2012]. Bagheri et al [2014] reported that spraying with 20% (v/v) methanol in lavender greatly increased leaf area, leaf fresh and dry mass.…”
Section: Introductionmentioning
confidence: 99%
“…Bean is a 3-carbon plant; as such, it has high tolerance to severe heat, water stress, and intense light as it breathes optically due to decreased concentration of CO 2 in the leaves and increased oxygen supply. Photorespiration can cause a 20% loss of carbon in a plant that eventually results in decreased performance (Hosseinzadeh et al, 2016). Drought stress is a typical environmental stress that has an adverse effect on the performance of bean that can be as much as 25% (Ahmadpour et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Many researchers have reported that application of methanol, as a source of carbon for cultivated plants, is now widespread practice (Benson and Nonomura, 1994, Downie et al, 2004, Hosseinzadeh et al, 2012. Plants are easily able to absorb methanol sprayed on leaves that is then used by the plant as a source of carbon.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations